Pendampingan Perilaku Hidup Bersih dan Sehat di Pondok Pesantren Al-Ittihad Poncokusumo Malang - Bisma Azhar Ramadhan; Muhammad Fauzul Adhim; Azizah, Khisna (STAI Ma'had Aly Al-Hikam Malang, 2025)
Abstract The optimization of Clean and Healthy Living Behavior at Al-Ittihad Islamic Boarding School, Poncokusumo, aims to maximize education and mentoring to improve the health quality of students. This program is designed to raise awareness of the importance of cleanliness and health through educational approaches such as interactive seminars, educational media in the form of posters, and improved hygiene facilities. This approach is strengthened by Asset-Based Community Development (ABCD) to empower the local assets of the boarding school. Over the course of onemonth, intensive mentoring was carried out through routine activities such as roan (communal cleaning), health exercises, the installation of educational stickers, and regular evaluations. The results showed increased awareness and participation of students in implementing PHBS. Collaboration among students, administrators, and the boarding school community served as a key indicator of the program's success. Ongoing education and mentoring proved effective in creating a clean, healthy, and comfortable environment, while also shaping a healthy and productive young generation. This program can serve as a model for other boarding schools in supporting the health of the nation's future generations. Keywords: PHBS, Islamic Boarding School, Education, Mentoring Abstrak Optimalisasi Perilaku Hidup Bersih dan Sehat di Pondok Pesantren Al-Ittihad Poncokusumo bertujuan untuk memaksimalkan edukasi dan pendampingan dalam meningkatkan kualitas kesehatan santri. Program ini dirancang untuk membangun kesadaran akan pentingnya kebersihan dan kesehatan melalui pendekatan edukatif, seperti seminar interaktif, media edukasi berupa poster, dan peningkatan fasilitas kebersihan. Pendekatan ini diperkuat dengan Asset-Based Community Development (ABCD) untuk memberdayakan aset lokal pesantren. Selama satu bulan, pendampingan intensif dilakukan melalui kegiatan rutin seperti ro’an, senam sehat, pemasangan stiker edukasi, dan evaluasi berkala. Hasilnya menunjukkan peningkatan kesadaran dan partisipasi santri dalam menerapkan PHBS. Kolaborasi antara santri, pengurus, dan pihak pesantren menjadi indikator keberhasilan program ini. Edukasi dan pendampingan berkelanjutan terbukti efektif dalam menciptakan lingkungan pesantren yang bersih, sehat, dan nyaman, sekaligus membentuk generasi muda yang sehat dan produktif. Program ini dapat menjadi model bagi pesantren lainnya dalam mendukung kesehatan generasi penerus bangsa. Kata Kunci: PHBS, Pondok Pesantren, Edukasi, Pendampingan